Factors Affecting Student Anxiety in Completing the Final Project - Neiliel Fitriana Anies; Junizar Junizar; Rizaldi Nanda Wiguna (GLOBAL HEALTH SCIENCE GROUP, 2025)
One of the graduation requirements for final-year students is completing a final project in the form of a Scientific Paper (Karya Tulis Ilmiah or KTI). The purpose of this study was to investigate ehat factors influence students’ anxiety in the process of completing a final project. The research method used was quantitative with a cross-sectional study design with a sample of 155 final year students who were preparing their final project at Akper Kesdam Iskandar Banda Aceh. Anxiety was measured using the Depression Anxiety Stress Scale 21 (DASS) 21 questionnaire. Data analysis using Chi-square using SPSS software. The result of the study explained that there was a significant relationship between family factors, peers, supervisors and environtment with the anxiety of students who completed their final project with p value <0,05. This study recommends future researchers to conduct experimental studies as a form of effort to overcome students’ anxiety in completing their final project.